Penerapan Metode Berbicara Tentang Hewan Terhadap Perkembangan Sosial Emosional Anak Usia Dini Di PAUD Nurul Hikmah Desa Tanjung Harapan Kecamatan Kampar Kiri Kabupaten Kampar - Inmaryanto, Inmaryanto; Nikmah, Nikmah; Andani, Winda (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2022)
This study aims to determine the application of the method of talking about animals to the socio-emotional development of early childhood in PAUD Nurul Hikmah Tanjung Harapan Village, Kampar Kiri District, Kampar Regency. This type of research is classroom action research (CAR). The results showed that the results of observing children's gross motor activity increased after using clogs as a game to motivate children's gross motor skills in students at Mutiara Kindergarten. This can be seen from the initial data to cycle II meeting 2. Initial data 43.83%, Cycle II meeting 2 obtained an average percentage of 86.36%. So that the overall increase in teacher activity obtained an average percentage of 42.53%